The analysis of short supply chain patterns in urban vegetable stalls and its contributions to sustainable development goals - Ivana Arviani Tan; Rustina Untari (EcoProfit: Sustainable and Environment Business, 2026)
Background: The long supply chain of the global food system faces criticism of poverty, which has led to the emergence of short supply chains (SSC) as an alternative. The urban system, particularly in Semarang City, still needs improvement because currently, food is still supplied from agricultural areas outside the city due to the city's inadequate conditions for farmed food. This study investigates the implementation of SSC through emerging urban vegetable stalls ("kedai sayur") in Semarang City, Indonesia, a growing urban center that relies on surrounding agricultural areas. Methods: A qualitative case study approach was used, utilizing semi-structured interviews and participant observation with eight vegetable stalls selected purposively in five geographical regions of Semarang City—north (North Semarang Subdistrict), east (Gayamsari and Pedurungan Subdistrict), south (Banyumanik and Gajahmungkur Subdistrict), west (West Semarang Subdistrict), and central (Central Semarang Subdistrict)—to understand their operational and supply chains patterns. Findings: The research identified four distinct SSC patterns, adapted to local contexts, which effectively reduce intermediaries and enhance vegetable freshness. These patterns demonstrably contribute to Sustainable Development Goals (SDGs) 2, 11, and 12 by improving food access, strengthening urban-rural linkages, and promoting responsible consumption. However, a key finding is the environmental trade-off: reliance on small-scale, fragmented logistics can lead to higher carbon emissions per unit, presenting a risk of unintentional greenwashing. Conclusion. Vegetable stalls represent a significant innovation for urban food security, achieving their full sustainability potential requires coordinated logistics solutions, such as shared transport, to mitigate hidden environmental costs and ensure authentic sustainable development. Novelty/Originality: This study bridges the gap between urban food security and sustainable logistics by analyzing the "kedai sayur" (vegetable stall) phenomenon in Semarang City.